Fintech, Banking Factors, and Economic Drivers of Efficiency in Jordan’s Banking Sector: Insights from DEA, SBM, and Logit Models - Obeid, Rami (International Journal of Economics and Financial Issues, 2025)
The study aims to evaluate the efficiency of the banking sector in Jordan from 2011 to 2022, employing the Data Envelopment Analysis (DEA) methodology, Slacks-Based Models (SBM), and Logit regression models. The findings show that, overall, the Jordanian banking sector demonstrates high efficiency, though there is variation across individual banks, despite the economic and geopolitical challenges faced during the study period. The study also examines the factors influencing the efficiency of Jordanian commercial banks, including banking and economic variables, as well as the impact of the COVID-19 pandemic. The results reveal that capital adequacy and Fintech adoption have the most significant positive effect on bank efficiency, while market concentration, measured by the Herfindahl-Hirschman Index (HHI), has the most substantial negative impact. The paper emphasizes the importance of continuous improvements in risk management, technological adoption, and operational efficiency, as well as fostering greater competition between banks. Additionally, it highlights the critical role of macroeconomic stability in supporting long-term banking sector efficiency.